2018
DOI: 10.3892/mmr.2018.9261
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M promotes the osteogenic differentiation of mouse MC3T3‑E1osteoblasts through the regulation of monocyte chemotactic protein‑1

Abstract: The present study investigated the function of oncostatin M (OSM), which may be associated with monocyte chemotactic protein-1 (MCP-1), on mouse MC3T3-E1 osteoblast development and bone remodeling. Levels of MCP-1, macrophage inflammatory protein 1α (MIP1α) and regulated upon activation normal T cell expressed and secreted (RANTES) were measured by ELISA. Cell viability, migration and invasion abilities were detected by MTT, wound healing and Transwell assays, respectively. Western blotting was performed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Several scholars have studied the osteogenic differentiation mechanism of OSM on MC3T3-E1 cells. Zheng et al (59) revealed that OSM promoted the osteogenic differentiation of MC3T3-E1 through MMP-1. It has also been found that Notch signaling pathway plays a negative regulatory role in OSM promoting MC3T3-E1 osteogenic differentiation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have studied the osteogenic differentiation mechanism of OSM on MC3T3-E1 cells. Zheng et al (59) revealed that OSM promoted the osteogenic differentiation of MC3T3-E1 through MMP-1. It has also been found that Notch signaling pathway plays a negative regulatory role in OSM promoting MC3T3-E1 osteogenic differentiation (24).…”
Section: Discussionmentioning
confidence: 99%
“…36 Besides, oncostatin M (OSM) is a member of IL-6 family and induces matrix metalloproteinases (MMPs) expression in a variety of animal cells. [37][38][39] Increased OSM was found in gingival crevicular fluid in periodontitis patients. Simultaneously, exposed to T. d in vitro increased the synthesis and release of OSM in Mϕs.…”
Section: Aggravation Of Periodontal Inflammationmentioning
confidence: 94%
“…In addition, P. g might control the plasticity of Mϕs by preventing the Mϕs from transforming into the M2 subtype in the tissue and redirecting M2 cells to be polarized to the pro‐inflammatory M1 subtype, leading to an over‐inflammatory environment, impairing Mϕs’ ability to repair damaged periodontal tissues 36 . Besides, oncostatin M (OSM) is a member of IL‐6 family and induces matrix metalloproteinases (MMPs) expression in a variety of animal cells 37–39 . Increased OSM was found in gingival crevicular fluid in periodontitis patients.…”
Section: The Role Of Mϕs In Periodontitismentioning
confidence: 99%
“…OSM also has the ability to promote the proliferation and osteogenic differentiation of osteoblasts. OSM can promote osteogenic differentiation of mouse embryo osteoblast precursor cells MC3T3-E1 by regulating CCL2 (74). Additionally, OSM can promote osteoclast differentiation.…”
Section: Osm Signaling and Bone Homeostasis And Cartilage Metabolismmentioning
confidence: 99%